The impact of simulation-based triage education on nursing students' self-reported clinical reasoning ability: A quasi-experimental study. (January 2021) - Hu, Fen; Yang, Jian; Yang, Bing Xiang; Zhang, Feng-Jiang; Yu, Si-Hong; Liu, Qian; Wang, Ai-Ling; Luo, Dan; Zhu, Xiao-Ping; Chen, Jie
Abstract: Few studies have comprehensively examined the effectiveness of simulation-based triage education on clinical reasoning of nursing students. This study evaluated the impact of a simulation-based triage exercise on nursing students' self-reported clinical reasoning ability. Three cohorts of third-year nursing students were divided into intervention group a (IG a, n = 62), intervention group b (IG b, n = 57), and a control group (CG, n = 53). Students in IG a and IG b participated in a simulation-based triage education consisting of 2 h of multiple patient triage simulations and an hour of structured debriefing. The CG participated in a traditional didactic triage course consisting of a 3-h lecture. Self-reported clinical reasoning ability in pre and post-triage education was measured by the Nurses Clinical Reasoning Scale. There was no significant difference in mean clinical reasoning ability scores between the three groups in pre-test ( p  > 0.05). Clinical reasoning ability scores in post-test among students in IG a and IG b were significantly higher than those in CG ( p  < 0.001). Nursing students exposed to a simulation-based triage education had more improvement in self-reported clinical reasoning ability as compared with students who participated in a lecture-based triage education program. Highlights: Simulation-based triage education improved nursing students' self-reported clinical reasoning ability. Nursing students integrated clinical reasoning into principles of triage during simulation and debriefing. Nurses in emergency departments and intensive care units may benefit from this triage simulation.